THE LIMIT OF LAND REGULARISATION AS POVERTY ALLEVIATION STRATEGY IN INFORMAL SETTLEMENTS: EMPIRICAL EVIDENCE FROM LAGOS, NIGERIA - Muyiwa E. AGUNBIADE; Oluwafemi A. OLAJIDE; Hakeem BISHI (Journal of Construction Project Management and Innovation)
Some studies have linked land titling to economic growth and poverty alleviation through access to credit facilities, housing improvement and security against eviction. However, many other studies have equally argued otherwise. It remains an ongoing debate. This paper, contributes to the ongoing debate on the nexus between land titles and poverty alleviation in informal settlements. It demonstrates that land titling, on its own, will not necessarily leads to poverty alleviation, as the intended beneficiaries are largely not interested in the programme. In addition, empirical evidence from Lagos and some other developing regions of the world suggests that land tiling has not and may not achieve many of the benefits appropriated to it by its proponents. Where it seems to have achieved some of its benefits, it has largely not been to the advantage of the poor. This paper, therefore, concludes that the policymaker must exercise caution on the issue of land titling as a solution to the endemic poverty in informal settlements. They should also explore the option of land tenure continuum. It recommends that an effective poverty alleviation strategy must incorporate the range of assets required to build a sustainable livelihood. It must also take into considerations the complexity of vulnerabilities the urban poor encounter as they pursue their livelihoods objectives.